2014
DOI: 10.1371/journal.pone.0098367
|View full text |Cite
|
Sign up to set email alerts
|

The Gluconeogenesis Pathway Is Involved in Maintenance of Enterohaemorrhagic Escherichia coli O157:H7 in Bovine Intestinal Content

Abstract: Enterohaemorrhagic Escherichia coli (EHEC) are responsible for outbreaks of food- and water-borne illness. The bovine gastrointestinal tract (GIT) is thought to be the principle reservoir of EHEC. Knowledge of the nutrients essential for EHEC growth and survival in the bovine intestine may help in developing strategies to limit their shedding in bovine faeces thus reducing the risk of human illnesses. To identify specific metabolic pathways induced in the animal GIT, the transcriptome profiles of EHEC O157:H7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 56 publications
(76 reference statements)
5
55
0
1
Order By: Relevance
“…Therefore, it is important to determine whether pathogens require glycolytic nutrients, gluconeogenic nutrients, or both for success in invading and subsequently colonizing the host. Indeed, recent studies have suggested that some pathogens use glycolytic nutrients, some use gluconeogenic nutrients, and some use both to adapt to diverse host habitats (1)(2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Therefore, it is important to determine whether pathogens require glycolytic nutrients, gluconeogenic nutrients, or both for success in invading and subsequently colonizing the host. Indeed, recent studies have suggested that some pathogens use glycolytic nutrients, some use gluconeogenic nutrients, and some use both to adapt to diverse host habitats (1)(2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…) while the genes encoding uptake or assimilation of this amino acid were not found differentially expressed in microarrays experiments when the bacteria reached the stationary growth phase (Bertin et al . ). Asparagine was poorly detected in BSIC‐LEM while the transcription of ansB that encodes asparaginase (deamination of asparagine to aspartate) was significantly induced in EHEC EDL933 during incubation in f‐BSIC (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Genes involved in the assimilation or transport of a limited number of amino acids are up-regulated in EHEC EDL933 during incubation in f-BSIC Whole transcriptomic profiling of the reference EHEC strain EDL933 incubated in bovine small intestinal content (BSIC) previously deposited in NCBI's GEO database (accession number GSE49468) (Bertin et al, 2014) revealed the induction of genes associated with amino acids transport and catabolism. In the current report, we performed an in depth analysis of the assimilation of free amino acids present in BSIC by EHEC EDL933.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, among the less abundant proteins, we only detected the homologous recombination pathway, which is extremely important for the accurate repair of DNA double-strand breaks (Figure 2C). Different studies have reported that glycolysis / gluconeogenesis pathway might influence in the colonization process of EHEC in the gastrointestinal tract of both mouse and bovine (20, 21). Although glycolysis substrates inhibit the expression of genes that are localized in locus of enterocyte effacement (LEE), this pathway plays an important role in the initial colonization and maintenance of EHEC in the mouse intestine.…”
Section: Resultsmentioning
confidence: 99%